Kajian Hermeneutika dalam Ilmu Al-Qur’an - Andi Warisno (Pascasarjana IAIN Metro, 2019)
This article attempts to show that hermeneutics as an approach in understanding the Qur‟an has been available in Ulum al-Qur‟an (the science of the Qur‟an). Hermeneutics is the art of interpreting the text. It is a theory imported from the West and has been implemented mostly to interpret the Bible. Many scholars who implemented this approach to investigate the Bible showed that Bible is no longer original and many alteration have been made to it. Thus, how could this approach be implemented to understand the Qur‟an? Will it reduce the divinity of the Qur‟an? This article shows that In fact if we look at the meaning of the hermeneutics as stated above, the procedural aspects in understanding the Qur‟an have been available in ulumul Qur‟an. The science of the Qur‟an has proven that the Qur‟an is sacred and divine. It is revealed from God to Muhammad through Jibril. Thus, there is no question of putting the Qur‟an less divine if we implement hermeneutical approach. It is just a matter of the term which previously unrecognised, but the practice has been implemented in ulum al-Qur‟an long ago.